Exploitation and new orientalism in Sam Kadi’s the citizen - Hanan Alaklook; Jamaluddin Aziz; Fauziah Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2016)
September 9 /2011 (henceforth 9/11) is a global cultural moment as it redefines the way America interprets the world and the way the world interprets the US. This is especially true in the representation of Arabs in Hollywood films as the Arabs were seen as the culprit of the momentous event. It inevitably cements the idea that the Arab as the other, this has become a fundamental structure of the American psyche. Pre 9/11, Hollywood has produced a significant amount of films covering Arab characters in a variety of Arab stereotypes, which were limited to what was known from the stories of the orientalist European and their legends about the mysterious East. We argue that while the negative stereotype continues in post 9/11 films, the ideological workings, however, are different. We have observed that Hollywood post 9/11 are keener to hire Arab actors to play Arab characters, which usually were played by Pakistani or non-Arab actors. Therefore, this paper examines the exploitation of Arab characters played by Arab actors in Hollywood films post 9/11 by focusing on The Citizen (2012) directed by Sam Kadi. Employing New Orientalism theory, this paper uses textual analysis as the method, focusing on how the Arab Characters are being exploited in this film.